2022
DOI: 10.3324/haematol.2022.282019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to venetoclax plus hypomethylating agent therapy and survival in blastphase myeloproliferative neoplasm

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 17 publications
(35 reference statements)
0
15
1
Order By: Relevance
“…The current retrospective experience with CPX-351 in patients with MPN-BP was not overtly different than previous observations in similar patients receiving standard 7 + 3 induction or HMA-Ven [4,5]. The observed CR/CRi rates with 7 + 3 induction and HMA-Ven were 35%/24% and 26%/17%, respectively [4,5].…”
Section: Dear Editorcontrasting
confidence: 57%
See 1 more Smart Citation
“…The current retrospective experience with CPX-351 in patients with MPN-BP was not overtly different than previous observations in similar patients receiving standard 7 + 3 induction or HMA-Ven [4,5]. The observed CR/CRi rates with 7 + 3 induction and HMA-Ven were 35%/24% and 26%/17%, respectively [4,5].…”
Section: Dear Editorcontrasting
confidence: 57%
“…Reported chemotherapeutic regimens for MPN-BP included either intensive acute myeloid leukemia (AML)-like induction chemotherapy with 7(cytarabine)+3(daunorubicin/idarubicin), or less intensive treatment with hypomethylating agent (HMA) based combinations with venetoclax (Ven) or ruxolitinib; associated CR/ CRi rates were 59% (AML-like induction), 43% (HMA-Ven) and 8% (HMA-ruxolitinib) [4][5][6][7]. CPX-351 (Vyxeos™) is a liposomal formulation of daunorubicin and cytarabine and is currently FDAapproved for elderly patients with secondary AML with myelodysplasia related changes and therapy-related AML.…”
Section: Dear Editormentioning
confidence: 99%
“…24 By contrast, the CR/CRi rate in a retrospective study of 47 patients with MPN-BP treated with Ven-HMA was reported at 43% and was higher than historically documented for HMA alone. 28 Furthermore, 7 of 13 (54%) transplant-eligible patients in CR/CRi, in the particular study, 28 were successfully bridged to ASCT. Unlike the case with Ven-HMA, preliminary reports on the use of CPX-351 in MPN-BP have not been as encouraging.…”
mentioning
confidence: 92%
“…In other words, a prospective controlled study is necessary to clarify the value of pre‐transplant bridging chemotherapy in both MPN‐BP and MPN‐AP. In the meantime, our current choice for pre‐transplant bridging chemotherapy is combination of Ven and HMA and we recommend an individualized approach in its implementation, based on bone marrow/circulating blast burden, likelihood of response, and risk of transplant‐barring complications associated with bridging chemotherapy 28 . Finally, post‐transplant management should include systematic monitoring of molecular or morphologic/clinical relapse and application of pre‐emptive or salvage donor lymphocyte infusions and second allograft in carefully selected patients 41 …”
mentioning
confidence: 99%
See 1 more Smart Citation